2019
DOI: 10.1016/j.pnpbp.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder with secondary psychotic features (PTSD-SP): Diagnostic and treatment challenges

Abstract: Trauma exposure leads to various psychiatric disorders including depression, anxiety, bipolar disorders, personality disorders, psychotic disorders, and trauma related disorders, especially posttraumatic stress disorder (PTSD). There are some overlapping symptoms of both PTSD and psychosis that make diagnosis challenging. Despite this overlap, the evidence of PTSD with comorbid psychosis as a distinct entity lies in the research showing biologic, genetic and treatment management differences between psychotic P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 87 publications
1
83
0
2
Order By: Relevance
“…While 15-64% of veterans with PTSD from Western countries have been reported to have PTSD-SP (David, Kutcher, Jackson, & Mellman, 1999;Kaštelan et al, 2007;Kozarić-Kovačić & Borovečki, 2005), a prevalence of 41% was found in a recent study among trauma-affected refugees with PTSD (Nygaard, Sonne, & Carlsson, 2017). It is still unclear whether PTSD-SP is related to a complex or chronic form of PTSD or indicative of severe PTSD (Compean & Hamner, 2019) and the diagnostic concept is not recognized in current nosological systems.…”
Section: 受创伤的难民中奖赏神经加工与创伤后应激障碍和继发性精神病症状的 关联mentioning
confidence: 99%
See 3 more Smart Citations
“…While 15-64% of veterans with PTSD from Western countries have been reported to have PTSD-SP (David, Kutcher, Jackson, & Mellman, 1999;Kaštelan et al, 2007;Kozarić-Kovačić & Borovečki, 2005), a prevalence of 41% was found in a recent study among trauma-affected refugees with PTSD (Nygaard, Sonne, & Carlsson, 2017). It is still unclear whether PTSD-SP is related to a complex or chronic form of PTSD or indicative of severe PTSD (Compean & Hamner, 2019) and the diagnostic concept is not recognized in current nosological systems.…”
Section: 受创伤的难民中奖赏神经加工与创伤后应激障碍和继发性精神病症状的 关联mentioning
confidence: 99%
“…PTSD is a diagnosis characterized by intrusive thoughts, avoidance, negative mood, and cognitive alterations, as well as arousal and reactivity in response to a psychologically traumatic experience (DSM-5) (APA, 2013). Secondary psychotic symptoms (PTSD-SP) may occur, and suggested criteria include, among others, that PTSD symptoms precede the onset of psychotic symptoms and that the criteria for another psychotic psychiatric condition are not met (Compean & Hamner, 2019). Estimates of PTSD-SP varies across studies, possibly reflecting variations in the PTSD-SP criteria.…”
Section: 受创伤的难民中奖赏神经加工与创伤后应激障碍和继发性精神病症状的 关联mentioning
confidence: 99%
See 2 more Smart Citations
“…Trauma exposure leads to various psychiatric disorders including depression, anxiety, bipolar disorders, personality disorders, psychotic disorders, and traumarelated disorders, especially post-traumatic stress disorder [3]. Post-traumatic stress disorder is classified in the new class of traumatic and stress disorder [4].…”
Section: Ptsdmentioning
confidence: 99%